Využití informačních systémů v drobném a středním podnikání - Myšková, Renáta (Univerzita Pardubice, 1999)
In the period of the information explosion, small and medium-sized companies are constantly made to use information systems for classification and evaluation of gathered information. This appers to be the beginning of the need of their flexibility in terms of the market demands. The pressure on the quality, quantity rising. This concerns any business regardless of its size. However, the quantitative growth of data is mostly not balanced by equal growth of quality of the information for the purpose of effective management. This is why it is very important to monitor the overall information about a company in small and medium-sized business. Effective use of the gathered information depends on the choice of the information system corresponding to the company structure.
Keywords: Podnikání; Informační systémy; malé a střední podniky; řízení; Komunikace